Evaluation of the Impact of Tourism on Environmental Sustainability at the Situ Bagendit Tourist Destination - Adiatma, Dani; Rukma, Deden Firman Syuyaman (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2024)
This research evaluates the impact of tourism on environmental sustainability at Situ Bagendit, a natural tourist destination in Garut Regency, West Java. The increase in tourist numbers has led to both positive and negative environmental impacts, such as water pollution, waste accumulation, and ecosystem degradation. The mixed-methods approach used in this study involved field observations, interviews with local stakeholders, and surveys with tourists and residents. The findings indicate significant challenges, including pollution from motorized boats and inadequate waste management, but also highlight increased community awareness and sustainable initiatives. The study recommends improvements in environmental regulations, waste management systems, and educational programs for tourists.